Asesmen Nasional: Tolok Ukur Kualitas Pendidikan Indonesia ? - Desya Nathasya Ramadiana; Masduki Asbari; Risha Putri Laksana (AGUSPATI RESEARCH INSTITUTA, 2024)
The aim of this study is to measure the quality of education in schools. In this study report, a qualitative descriptive method was used by observing closely because the data source was obtained by listening to the oral narrative from the Indonesian Ministry of Education and Culture's YouTube channel entitled